(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Introduction : Adopting optimal breast feeding practices is fundamental right to a child’s survival, growth and development. Despite all the potential benefits, only about two fifths of infants 0-6 months of age worldwide are exclusively breastfed. Analysis of data on feeding practices among infants highlights the need for accelerated programming in this area. Present study was aimed to survey feeding practices in infants up to 6 months and observing variables for faulty feeding practices Method :Mother of infants up to 6 months coming from urban area in a tertiary care hospital were interviewed for feeding practices as per preformed questionnaires. If feeding practices were faulty all details regarding various factors leading to same were asked and analysed. Results :Total 518 mothers were interviewed. Only 37% infants were exclusively breast feed, in 29% feeding was started in 1st hour of life and in 25% some form of prelacteal feeds were given. On analysing different factors for faulty feeding practices we found that primigravida, CS delivery, (p<0.001)different myths regarding mother health, baby health, and breast feeding, lack of awareness ,faulty feeding techniques, low socioeconomic status(65%) and poor education(80%) were contributing factors leading to same. There were multiples factors in single mother for faulty feeding practices. Conclusion : Promotion, support and adherence to recommendations of breast feeding is still a gold standard to gain optimal growth and development of children. still health personnel has to do lot more to particularly in field of proper education, explanation and demonstration in field of same. Using newer media technology like mobile and TV will be helpful to spread it fast.